2015
DOI: 10.1007/978-3-319-15895-2_26
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Processes and Deviations

Abstract: In process mining, one of the main challenges is to discover a process model, while balancing several quality criteria. This often requires repeatedly setting parameters, discovering a map and evaluating it, which we refer to as process exploration. Commercial process mining tools like Disco, Perceptive and Celonis are easy to use and have many features, such as log animation, immediate parameter feedback and extensive filtering options, but the resulting maps usually have no executable semantics and due to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 18 publications
0
37
0
1
Order By: Relevance
“…Many mining algorithms only have an implicit notion of state, i.e. the focus is on learning the ordering of activities [11,16]. However, process state information may actually be present explicitly in information systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many mining algorithms only have an implicit notion of state, i.e. the focus is on learning the ordering of activities [11,16]. However, process state information may actually be present explicitly in information systems.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of process mining is to provide fact-based insights into the execution of processes [1,11,13]. An important aspect of this is the discovery of process models based on behaviour captured in event data.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding decision mining, the algorithm that generates the petri net model should be selected first. Authors reject the algorithms presented in [10] and select the inductive visual miner [11] as the petri net model generator. Indeed, experience has shown that only the inductive visual miner allows the inclusive gateways to be identified by the decision mining algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…To automatically generate a petri net model from an event log, different algorithms were proposed. The alpha algorithm, alpha++ algorithm, ILP miner, genetic miner, among others, are presented in [10], and the inductive visual miner that was recently proposed in [11].…”
Section: Decision Miningmentioning
confidence: 99%
“…5, is not present in this mined model. This is partially related to the mining algorithm used to discover the model, the Inductive visual Miner [23]. This algorithm, like many others, has difficulties incorporating duplicate activities in the model and many forms of motion occurring during the preparation phase are similar to those occurring during the aftercare.…”
Section: B Discovering Models Of Smart Bottle User Behaviourmentioning
confidence: 99%